Islamic Education Reform: Assessing the Thoughts of Kh. Abdul Wahid Hasyim - Sabar; Yulita Putri; Abid Nurhuda; Anastasia (MultiTech Publisher, 2023)
Islamic education was built with great struggle from the Dutch and Japanese eras to the time of Indonesian independence. And in the early era of its reign, Japan sought the attention of Muslims by giving its leaders the power and freedom to teach and spread their thoughts, especially matters related to Islamic education which always transformed from time to time until it was able to adjust to its development. One of the important figures in that era was KH Abdul Wahid Hasyim. So the purpose of this study is to describe Islamic Education Renewal: Examining KH's Thoughts. Abdul Wahid Hasyim. This type of research is a literature study with content analysis techniques and then conclusions. The results of the research show that the renewal of Islamic education according to KH. Abdul Wahid Hasyim covers the renewal of the pesantren education system in the institutional, methodological, curriculum, and library fields. As well as reforms in the national education system, including the obligation to study at madrasas, the inclusion of general education at madrasas/Islamic boarding schools, the inclusion of religious education in public schools, and the establishment of many Islamic tertiary institutions in Indonesia.